Treatment with Dexamethasone and Monophosphoryl Lipid A Removes Disease-Associated Transcriptional Signatures in Monocyte-Derived Dendritic Cells from Rheumatoid Arthritis Patients and Confers Tolerogenic Features - García-González, Paulina A.; Schinnerling, Katina; Sepúlveda-Gutiérrez, Alejandro; Maggi, Jaxaira; Hoyos, Lorena; Morales, Rodrigo A.; Mehdi, Ahmed M.; Nel, Hendrik J.; Soto, Lilian; Pesce, Bárbara; Molina, María Carmen; Cuchacovich, Miguel; et al. (Frontiers in Immunology, 2016)
Tolerogenic dendritic cells (TolDCs) are promising tools for therapy of autoimmune diseases such as rheumatoid arthritis (RA). Here we characterise monocyte-derived TolDCs from RA patients modulated with dexamethasone and activated with monophosphoryl lipid A (MPLA), referred to as MPLA-tDCs, in terms of gene expression, phenotype, cytokine profile, migratory properties and T cell-stimulatory capacity, in order to explore their suitability for cellular therapy. MPLA-tDCs derived from RA patients displayed an anti-inflammatory profile with reduced expression of costimulatory molecules and high IL-10/IL-12 ratio, but were capable of migrating towards the lymphoid chemokines CXCL12 and CCL19. These MPLA-tDCs induced hyporesponsiveness of autologous CD4+ T cells specific for synovial antigens in vitro. Global transcriptome analysis confirmed a unique transcriptional profile of MPLA-tDCs and revealed that RA-associated genes, which were upregulated in untreated DCs from RA patients, returned to expression levels of healthy donor-derived DCs after treatment with dexamethasone and MPLA. Thus, monocyte-derived DCs from RA patients have the capacity to develop tolerogenic features at transcriptional as well as at translational level, when modulated with dexamethasone and MPLA, overcoming disease-related effects. Furthermore, the ability of MPLA-tDCs to impair T cell responses to synovial antigens validates their potential as cellular treatment for RA.